2021
DOI: 10.12791/ksbec.2021.30.3.237
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Stem Number on Growth, Fruit Quality, and Yield of Sweet Peppers Grown in Greenhouses under Supplemental Lighting with High Pressure Sodium Lamps in Winter

Abstract: The objective of this study was to evaluate the effect of stem number on plant growth, fruit quality, and yield of sweet peppers grown in greenhouses under supplemental lighting in winter. The seedlings were transplanted at 3.2 plants•m -2 on October 26, 2020, and started supplemental lighting with 32 high pressure sodium lamps for 16-hour photoperiod from December 1, 2020 to May 25, 2021. Stems were differently trained with 2 and 3 numbers after branching nodes were developed. In the final harvest, the plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Additional key words: climate control, CO 2 concentration, diffused glass, humidity deficit, ventilation 서 언 시설과채류의 대표적인 파프리카는 재배면적과 더불어 총 생산량이 지속적으로 증가하고있으며 고부가가치 작물로서 주목 받고있다(KATI, 2021; Yoon et al, 2021). 파프리카의 수량은 광, 온 ․ 습도, CO 2와 같은 환경요인들에 영향을 받는다 (Jeong et al, 2009).…”
Section: 동절기 반밀폐형 온실과 일반형 온실의 시설 내부 기상 환경 비교unclassified
“…Additional key words: climate control, CO 2 concentration, diffused glass, humidity deficit, ventilation 서 언 시설과채류의 대표적인 파프리카는 재배면적과 더불어 총 생산량이 지속적으로 증가하고있으며 고부가가치 작물로서 주목 받고있다(KATI, 2021; Yoon et al, 2021). 파프리카의 수량은 광, 온 ․ 습도, CO 2와 같은 환경요인들에 영향을 받는다 (Jeong et al, 2009).…”
Section: 동절기 반밀폐형 온실과 일반형 온실의 시설 내부 기상 환경 비교unclassified
“…The study of Yap et al [22] demonstrated that pepper fruit yield was higher in the blue light treatment compared to either red or red and blue light treatments. Some studies also investigated the effects of supplemental lighting on sweet pepper production in hydroponic culture [23][24][25]. However, previous investigation has paid little attention to pepper cultivar biomass of separate plant parts in relation to their water use under supplementary light treatments in a hydroponic system.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean and Jordan Valley, which have a relatively high amount of solar radiation, supplemental LED lighting was used for the purpose of increasing yields, while in other studies, it was hypothesized that supplemental LED lighting could improve the yield, total soluble solids, and ascorbic acid parameters of greenhouse tomato plants even in extremely hot summers when shading is needed [19,20,24]. In paprika cultivation in Korea, supplemental lighting has been mostly applied to winter cultivation, which presents low solar radiation [25][26][27]. Nevertheless, the hot period is considered in this approach, and supplemental lighting is used during the rainy season, which has a low amount of solar radiation, so an increase in both quantity and quality can also be expected in summer cultivation.…”
Section: Introductionmentioning
confidence: 99%